Microdomain structure in polylactide-block-poly(ethylene oxide) copolymer films - Kubies, D; Rypácek, F; Kovárová, J; Lednický, F (Biomaterials, 2000)
Structured surface is an important property of polymer biomaterials for tissue engineering, for its capacity to expose domains with different surface energy and functional groups. For this purpose, amphiphilic A-B-A block copolymers with polylactide (PLA) as A blocks and poly(ethylene oxide) (PEO 3, Mn = 3090; PEO6, Mn = 6110) as B block were synthesized by ring-opening polymerization of either L-lactide (L-LA) or DL-lactide (DL-LA), using poly(ethylene glycol)s as macroinitiators and tin(II) octanoate (Sn(Oct)2) as a catalyst. Differential scanning calorimetry (DSC) and electron microscopy were used to study the phase separation of the hydrophobic (PLA) and hydrophilic (PEO) segments in films made of the copolymers and their blends with high-molecular-weight PLA homopolymers. Hydrophilic (PEO) and hydrophobic (PLA) domains were formed at the polymer film surface due to the separation of phases. The phase separation was affected by the copolymer composition and the stereoregularity of PLA blocks in the copolymers.
Keywords: gelová chromatografie; Microscopy, Electron; Polyesters; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; epoxidové sloučeniny; viskozita; testování materiálů; Microscopy, Electron, Scanning; Viscosity; magnetická rezonanční spektroskopie; Biocompatible Materials; polyestery; mikroskopie elektronová rastrovací; biokompatibilní materiály; elektronová mikroskopie; Epoxy Compounds; Magnetic Resonance Spectroscopy; Chromatography, Gel; Materials Testing